Effect of nitrogen source on soil nitrate concentration and yield, and quality of intermediate-day onions - Machado, RMA (2013)
Abstract The effect of nitrogen source application, broadcast onto the planting bed during the growing phase, on soil nitrate concentration, soil pH, yield, and quality of intermediate-day onions was evaluated in a field experiment in southern Portugal. In addition, the soil potential for providing nitrate-N to the crop along the growing season was also monitored. The field trial consisted of six treatments of different combinations of ammonium nitrate (17% NH4-N + 17% NO3-N) (AN) and ammonium sulphate (20.5 % NH4-N and 60% SO3) (AS) as fertilizers. Soil NO3-N and soil pH were measured at 0, 47, 76, 95, and 124 days after transplanting (DAT). Nitrogen source did not significantly affect the soil nitrate concentration, commercial yield, bulb dry weight, soluble solids or pH. AS-AS application as compared with AN-AN led to a significantly decrease in soil pH. The nitrate release through the mineralization of organic matter began in the first 47 DAT and occurred throughout the growing season. At 0 to 10 cm soil depth from 0 to 47 DAT, nitrate concentration increased by 14.8 mg kg-1. A significant amount of N uptake was provided by the soil, achieving a high commercial yield of 7.52 kg m-2 in the treatment without nitrogen application and 9.05 kg m-2 where N (45kg N/ha) was applied